Inhibition of hepatocyte growth factor/c-Met signalling abrogates joint destruction by suppressing monocyte migration in rheumatoid arthritis. (8th August 2020) - Hosonuma, Masahiro; Sakai, Nobuhiro; Furuya, Hidekazu; Kurotaki, Yutaro; Sato, Yurie; Handa, Kazuaki; Dodo, Yusuke; Ishikawa, Koji; Tsubokura, Yumi; Negishi-Koga, Takako; Tsuji, Mayumi; Kasama, Tsuyoshi; et al.
Abstract: Objectives: To determine the expression of hepatocyte growth factor (HGF) in RA biological fluids, the role of HGF in monocyte migration and the therapeutic effect of the c-Met inhibitor savolitinib in an arthritis model mice. Methods: HGF/c-Met expression in serum, SF and synovial tissues (STs) obtained from RA patients and controls, as well as RA fibroblast-like synoviocytes (FLSs), was evaluated by ELISA and immunostaining. To determine the function of HGF in RA SF, we preincubated RA SF with a neutralizing anti-HGF antibody and measured the chemotactic ability of a human acute monocytic leukaemia cell line (THP-1). Additionally, examinations were conducted of SKG mice treated with savolitinib for 4 weeks. Results: HGF levels in serum from RA patients were significantly higher than those in the controls and were decreased by drug treatment for 24 weeks. Additionally, the HGF level in SF from RA patients was higher than that in SF from OA patients. HGF and c-Met expression was also noted in RA STs. Stimulation of RA FLSs with TNF-α increased HGF/c-Met expression in a concentration-dependent manner, and c-Met signal inhibition suppressed production of fractalkine/CX3CL1 and macrophage inflammatory protein-1α/CCL3. When HGF was removed by immunoprecipitation, migration of THP-1 in RA SF was suppressed. In SKG mice, savolitinib significantly suppressed ankle bone destruction on µCT, with an associated reduction in the number of tartrate-resistant acid phosphatase-positive osteoclasts. Conclusion: HGF produced by inflammation in synovium of RA patients activates monocyte migration to synovium and promotes bone destruction via a chemotactic effect and enhanced chemokine production.